OPTIMALISASI KETERAMPILAN MOTORIK HALUS ANAK USIA DINI MELALUI ECOPRINT DENGAN TEKNIK POUNDING STUDI PARTISIPATIF DI DESA SINARJAYA PANDEGLANG - Helnanelis; Kartini, Etien; Susilawati; Maesaroh, Esa; Irfan , Muhamad (LPPM IAD Probolinggo, 2025)
Training fine motor skills from an early age is very important, as these abilities influence daily activities such as writing, drawing, and cutting. This activity employed the Participatory Action Research (PAR) method, carried out in stages—from situation analysis, focus group discussions, program implementation, to monitoring and evaluation. The program was conducted in Sinarjaya Village in the form of ecoprint training and mentoring. It involved one kindergarten (TK) and two Islamic kindergartens (RA), starting with teacher training followed by direct mentoring for children. Utilizing the abundant natural resources in the village, the ecoprint activity was carried out using the pounding technique, which involves hammering leaves onto fabric to create natural patterns. This process encourages children to actively move their fingers and wrists, making it highly effective for training small muscle movements. The assessment focused on the composition of colors and shapes, children’s consistency during the activity, and their creativity and neatness. This activity not only improved children’s fine motor skills but also raised awareness among educators about how the surrounding environment can be used as a fun and engaging learning medium. The children showed enthusiasm, consistency, and enjoyed the learning process without boredom. Ecoprint with the pounding technique became a creative and meaningful educational experience. Keywords: Early childhood; Fine motor skills; Pounding technique.